2013
DOI: 10.3329/bjn.v28i1.17190
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Aneurysms: Acute VS Delayed Surgery - An Analysis of 52 Cases

Abstract: Introduction:Aneurysms resemble bubbles or focal dilation of arteries that occur at weak points of the artery wall (figure-1). There are many factors for its formation. These factors include genetic predisposition, the anatomy of the artery and its branches, 'wear-andtear' on the wall of the arteries due to blood flow, artery disease and cigarette smoking 1 . Aneurysms are the most common at circle of Willis in the central skull base. Approximately 80% of aneurysms arises from anterior circulation of the brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This is consistent with Reaz Mahmud et al where the average age was 48.24±9.26 35 . Another two studies conducted in Bangladeshthe mean age was 45.00±9.4 and 45.9 years 36,37 .In an epidemiological study done in India had shown average age of subarachnoid hemorrhage in their population was 49.63 years 38 .Worldwide the mean age of aneurysmal rupture is in the range of 50 to 55 years. The mean age of this study coincides with the both worldwide and sub-continent.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This is consistent with Reaz Mahmud et al where the average age was 48.24±9.26 35 . Another two studies conducted in Bangladeshthe mean age was 45.00±9.4 and 45.9 years 36,37 .In an epidemiological study done in India had shown average age of subarachnoid hemorrhage in their population was 49.63 years 38 .Worldwide the mean age of aneurysmal rupture is in the range of 50 to 55 years. The mean age of this study coincides with the both worldwide and sub-continent.…”
Section: Discussionmentioning
confidence: 96%
“…In this study 59.1% were hypertensive, 47.73% were smoker, 15.9% were alcoholic and were light drinker, 6.8% were substances abuser and 11.4% had positive family history of SAH. In Bangladesh a study of thirty SAH population revealed 44% of the patients had smoking habit and nearly half (46.7%) had hypertension 37 . Another study was conducted at Dhaka medical college and Hospital showed hypertension, smoking, diabetes mellitus and family history of SAH were found in 46.6%, 43.3%, 10.0% and 6.7% respectively 42 .…”
Section: Discussionmentioning
confidence: 99%
“…vent vasospasm, different pharmaceutical agents are used such as calcium channel blockers, magnesium sulphate, the statin agent, endothelin antagonists, and the nicardipine implants with extended releaese. However, their effects are limited and there are currently underway various studies about new drugs and treatments (29). The outcome of the disease is influenced by multiple immutable factors and factors that can be influenced by therapeutic interventions and their management.…”
Section: Hypothesesmentioning
confidence: 99%